Navigating Teachers’ Occupational Well-Being in the Tides of Classroom Processes and School Structures - Joy C. Nwoko; Emma Anderson; Oyelola Adegboye; Aduli E. O. Malau-Aduli; Bunmi S. Malau-Aduli (Education Sciences, 2024)
The well-being of primary school teachers is vital for fostering effective teaching and learning, yet they face a range of challenges that negatively impact their occupational health. This phenomenological study explores the multifaceted factors influencing teacher occupational well-being, with a focus on classroom processes and school-related factors. Employing a qualitative phenomenological approach, this study gathered in-depth insights from Australian primary school teachers through semi-structured interviews. Participants were recruited from a variety of educational settings to capture diverse experiences and perspectives. Data were thematically analysed to identify key themes impacting teacher well-being. The findings revealed significant challenges impacting teacher well-being, including the demands of individualised student needs, classroom dynamics, the role of school leadership, resource limitations, and the complexities of parental involvement. Teachers expressed a need for more relevant professional development programs and highlighted the importance of supportive leadership and adequate resources. Additionally, workload and the balance between professional and personal life emerged as critical factors influencing teacher well-being. This study underscores the importance of addressing the complex and interconnected factors that contribute to teacher well-being. Implications for educational practice include the need for supportive and communicative leadership, adequate professional development tailored to teachers’ needs, and the provision of sufficient resources to manage classroom diversity and demands. The findings advocate for systemic changes to foster a supportive educational environment that values and nurtures teacher well-being. Future research could explore effective strategies to support primary school teachers in their professional journeys.